2007
DOI: 10.1007/s11102-007-0036-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum IGF-I levels in the diagnosis and monitoring of acromegaly

Abstract: Insulin-Like Growth Factor-I (IGF-I) is a reliable marker of disease activity and growth hormone (GH) status in acromegaly, but its clinical utility has been hampered over the years by various issues including a lack of robust reference range data and variability in assay sensitivity and specificity. In acromegaly IGF-I correlates well with GH activity and nadir GH on oral glucose tolerance test (OGTT) and is the most sensitive and specific test in diagnosis, where serum IGF-I is persistently seen to be elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 82 publications
0
12
0
1
Order By: Relevance
“…Discordance between normalisation of the biochemical acromegaly status in regard to IGF1 and GH/nadir GH can be useful in the treatment and followup strategies, since elevated IGF1 alone seems to have a different prognosis compared with elevated GH/nadir GH alone (22,23). Patients with elevated IGF1 and normal GH/nadir GH are at risk of having persisting clinical manifestations of acromegaly and can therefore indeed benefit from the treatment with a GH receptor antagonist (24,25), while patients with elevated GH/nadir GH and normal IGF1 are at a risk of relapse of the tumour (22,23).…”
Section: Authorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Discordance between normalisation of the biochemical acromegaly status in regard to IGF1 and GH/nadir GH can be useful in the treatment and followup strategies, since elevated IGF1 alone seems to have a different prognosis compared with elevated GH/nadir GH alone (22,23). Patients with elevated IGF1 and normal GH/nadir GH are at risk of having persisting clinical manifestations of acromegaly and can therefore indeed benefit from the treatment with a GH receptor antagonist (24,25), while patients with elevated GH/nadir GH and normal IGF1 are at a risk of relapse of the tumour (22,23).…”
Section: Authorsmentioning
confidence: 99%
“…Patients with elevated IGF1 and normal GH/nadir GH are at risk of having persisting clinical manifestations of acromegaly and can therefore indeed benefit from the treatment with a GH receptor antagonist (24,25), while patients with elevated GH/nadir GH and normal IGF1 are at a risk of relapse of the tumour (22,23). The origin of discordance is likely to be that IGF1 and GH/nadir GH seem to represent two different aspects of acromegaly (26), and RT in general reduces rather than cures the hypersecretion of GH (3,24).…”
Section: Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Freda [24] concluded that a cutoff value of 1 µg/l fails to identify 50% of patients with active disease. Moreover, we must consider the influence of GH and IGF-1 levels in other conditions, such as diabetes mellitus, hepatic J Metabolic Synd ISSN: 2167-0943 JMS, an open access journal Pathophysiology and Treatment of Acromegaly or renal failure, hypothyroidism, pregnancy, adolescence, and anorexia nervosa, and that they are influenced by oral estrogen, age and sex [3,8,21,[23][24][25]. About 50% of patients with acromegaly experience a rapid increase in plasma GH concentrations after stimulation of the TRH secretion and/or gonadotropin-releasing hormone (GnRH) secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Acromegaly is associated with a 2-3-fold higher mortality rate and a reduction of life expectancy by 10-15 years compared with the general population. These outcomes are mainly attributed to the presence of other severe diseases, such as diabetes mellitus, hypertension, hyperlipidemia, cardiovascular and respiratory disease, and neoplasms [1,3,5,[7][8][9][10][11][12][13]. The duration of the disease is a prognostic factor.…”
Section: Introductionmentioning
confidence: 99%